Flowers retail trade market: an application of Porter’s Strategic Taxonomy - Anacleto, Adilson; Scheuer, Luciane; Cury, Amanda Casubek; de Oliveira, Luana Rodrigues de Azevedo (Ornamental Horticulture, 2020)
The flowers retail trade has shown good potential for development in agribusiness, despite the growth. Thus, in order to support a better understanding of the current scenario, it is presented the result of a research that sought to promote a classification by Porter’s Strategic Taxonomy, revealing what were the main lasting competitive advantages in the segment. In this context, a descriptive exploratory research was carried out between July and October 2019, where 23 flowers retailers in Paraná Coast, South of Brazil agreed to participate in the survey. The result of the classification of Porter’s taxonomy revealed that most retailers use the differentiation strategy (n = 52%), followed by the focus strategy (n = 48%), with no retailers that adopt the strategy of leadership in cost. The main threats from competitive forces were the bargaining power of the suppliers and the threat of substitute products. The main commercial tactics, which in the interviewees’ perception resulted in lasting competitive advantage, were the quality of the flowers sold, the experience in the flower segment that generated differentiated service, the offer of products different from the traditional ones and lower prices. The strategic typologies of Porter’s taxonomy adopted by retailers in Paraná Coast, in the current scenario, seem to be able to minimize the effects of competitive forces and they are able of generating sustainable competitive advantages.